Visual Analytics and knowledge creation from Big Data: A systematic review (Human Factors in Design, 2018)
This paper is about Visual Analytics: the use of visual resources to interpret information and create knowledge in Big Data. To identify the best practices in the area a systematic review of papers related to the topic was done. Some filters were used, such as: articles published at most 3 years ago, peer-reviewed, with title and abstract aligned with how to use Visual Analytics. As the main findings of the review we have: a) the prevalence of techniques using metaphors to monitor data through maps and dashboards; b) the need for specialists from different areas who can work with statistics applied to data interpretation. The paper finishes with suggestions of use of the findings and new research proposals concerning the creation of knowledge using Big Data.